Sulfasalazine Resolves Joint Stiffness in a Rabbit Model of Arthrofibrosis. Issue 3 (11th November 2019) - Atluri, Keerthi; Brouillette, Marc J.; Seol, Dongrim; Khorsand, Behnoush; Sander, Edward; Salem, Aliasger K.; Fredericks, Douglas; Petersen, Emily; Smith, Sonja; Fowler, Timothy P.; Martin, James A.
ABSTRACT: Joint stiffness due to fibrosis/capsule contracture is a seriously disabling complication of articular injury that surgical interventions often fail to completely resolve. Fibrosis/contracture is associated with the abnormal persistence of myofibroblasts, which over‐produce and contract collagen matrices. We hypothesized that intra‐articular therapy with drugs targeting myofibroblast survival (sulfasalazine), or collagen production (β‐aminopropionitrile and cis ‐hydroxyproline), would reduce joint stiffness in a rabbit model of fibrosis/contracture. Drugs were encapsulated in poly[lactic‐co‐glycolic] acid pellets and implanted in joints after fibrosis/contracture induction. Capsule α‐smooth muscle actin (α‐SMA) expression and intimal thickness were evaluated by immunohistochemistry and histomorphometry, respectively. Joint stiffness was quantified by flexion‐extension testing. Drawer tests were employed to determine if the drugs induced cruciate ligament laxity. Joint capsule fibroblasts were tested in vitro for contractile activity and α‐SMA expression. Stiffness in immobilized joints treated with blank pellets (control) was significantly higher than in non‐immobilized, untreated joints (normal) ( p = 0.0008), and higher than in immobilized joints treated with sulfasalazine ( p = 0.0065). None of the drugs caused significant cruciate ligament laxity. Intimal thickness was significantly lower than control in the normal and sulfasalazine‐treated groups ( p = 0.010 and 0.025, respectively). Contractile activity in the cells from controls was significantly increased versus normal ( p = 0.001). Sulfasalazine and β‐aminopropionitrile significantly inhibited this effect ( p = 0.005 and 0.0006, respectively). α‐SMA expression was significantly higher in control versus normal ( p = 0.0021) and versus sulfasalazine ( p = 0.0007). These findings support the conclusion that sulfasalazine reduced stiffness by clearing myofibroblasts from fibrotic joints. Statement of clinical significance: The results provide proof‐of‐concept that established joint stiffness can be resolved non‐surgically. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:629–638, 2020